The Tabon caves - Gibb, Hugh. ([Manila] Felta Book Sales, 1981)
Features the excavation of the Tabon caves and the cultural finds therein. Discusses the beliefs and practices of the Tagbanua associated with jars.
digitized copy : mp4
Keywords: Caves -- Philippines; Minorities; Ethnic group; Philippine history; Anthropology